Promoting regional tourism cooperation under CAREC 203 : a scoping study - Asian Development Bank (Philippines : Asian Development Bank, 2019)
This scoping study was prepared at the request of the member countries of the Central Asia Regional Economic Cooperation (CAREC) Program. The study seeks to assess the potential of CAREC as a platform to promote a regional approach to tourism development through the identification of opportunities for enhancing and expanding cooperation among member countries in the toursim sector, and to maximize economic opportunities while safeguarding ecosystems.
Introduction -- Current state of tourism and future prospects -- Strengths, weakness, opportunities and threats analysis -- Building on strengths and capturing opportunities -- Addressing weaknees and challenges -- Indentification of regional tourism cooperation : recommendations
Keywords: TOURISM